2020
DOI: 10.1177/2380084420940623
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Microbiota from Sjögren’s Syndrome Patients

Abstract: Objective: To compare the oral microbiota of Sjögren’s syndrome (SS) with that of healthy subjects (HS). Methods: Supragingival and subgingival biofilm samples were collected from the mesial-buccal tooth surfaces of SS patients (n = 57) and age- and sex-matched HS (n = 53). Unstimulated saliva and 8 oral tissue samples were taken using a buccal brush. Caries and periodontal measures were recorded. All supragingival samples and a subgroup of 24 SS and 28 HS subgingival samples, as well as 32 SS and 11 HS saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 36 publications
2
30
0
3
Order By: Relevance
“…We observed high levels of dipeptides, namely, tyrosine glutamine dipeptide, phenylalanine isoleucine dipeptide, and valine leucine dipeptide, and phenylalanine, in the saliva samples of patients with pSS. Previous reports have shown that pSS patients have dysbiosis in oral microbiota in bacterial species (e.g., Prevotella and Porphyromonas species) that can degrade proteins into smaller peptides and further into amino acids, such as phenylalanine [11,[13][14][15][16][17]. Moreover, high levels of dipeptides and phenylalanine in saliva have been associated with dysbiosis of oral microbiota in other oral pathologies, such as periodontitis [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…We observed high levels of dipeptides, namely, tyrosine glutamine dipeptide, phenylalanine isoleucine dipeptide, and valine leucine dipeptide, and phenylalanine, in the saliva samples of patients with pSS. Previous reports have shown that pSS patients have dysbiosis in oral microbiota in bacterial species (e.g., Prevotella and Porphyromonas species) that can degrade proteins into smaller peptides and further into amino acids, such as phenylalanine [11,[13][14][15][16][17]. Moreover, high levels of dipeptides and phenylalanine in saliva have been associated with dysbiosis of oral microbiota in other oral pathologies, such as periodontitis [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found lower Proteobacteria numbers and alpha diversity in the salivary microbiome of patients with SS and increased levels of Veillonella and Fusobacterium [51]. Veillonella parvula could be a potential biomarker for the early detection of SS [56]. P. gingivalis can induce reactivation of Epstein-Barr virus (EBV), a virus that is strongly implicated in the pathogenesis of both SLE and SS [48,57].…”
Section: Newly Emerging Connections Between Immune-mediated Inflammatmentioning
confidence: 99%
“…Existe um enorme esforço em compreender o papel das comunidades microbianas complexas, especialmente as microbiotas orais, na patogênese de várias doenças (Singh et al,2020). A cavidade oral apresenta diferentes sítios anatômicos como dentes, sulco gengival, língua, bochecha e palato, os quais representam nichos para estudo das interações comunidadehospedeiro que resultam em disbiose.…”
Section: Discussionunclassified
“…um estudo observacional(SINGH et al, 2020) realizado com o objetivo de comparar a microbiota oral da SS com a de indivíduos saudáveis, observou-se na avaliação do biofilme encontrado na superfície supragengival a presença de diversas espécies em níveis mais elevados em indivíduos saudáveis, incluindo Aggregatibacter actinomycetemcomitans, Campylobacter rectus, Eubacterium nodatum e Fusobacterium nucleatum polimorfo ss, sendo Veillonella a única espécie significativamente mais elevada em pacientes com Sjögren.…”
unclassified